Innate immunity in the brain in health and disease - Perry, V. Hugh (Henry Stewart Talks, 2009)
Macrophage populations in the brain, Regulation of brain macrophage-microglia phenotype, Inflammation in Alzheimer's disease, Prion disease, a model of chronic neurodegeneration, Behavioural assays, Impact of systemic infections/inflammation on the brain, Interactions between systemic inflammation and brain disease, Microglia switching, Relevance to Alzheimer's disease?, Impact of systemic infections on Alzheimer's disease progression